Analisis Kesalahan Berbahasa Dalam Skripsi Mahasiswa IAIN Sorong - Lalu Nasrulloh; Alif Hasanah; Ariyani Fatimah (Interference: Journal of Language, Literature, and Linguistics, 2022)
Abstract. The research, entitled Analysis of Language Errors in Thesis of IAIN Sorong Students, aims to find out language errors in the thesis of IAIN Sorong students seen from the use of spelling and linguistic level. This research is a qualitative research using descriptive analysis approach. Sources of data in this study are the text of the introduction and abstract of the thesis of IAIN Sorong students. The results of this study include language errors made by IAIN Sorong students, such as spelling errors which include errors in writing capital letters, periods, and commas. Errors in the use of language at the phonological level include errors in writing phonemes due to absorption elements, excess phoneme writing, and errors in writing standard words. Furthermore, errors in language use at the morphological level include affixation, preposition, and reduplication. Finally, errors in language use at the syntactic level are in the form of not saving words in sentences.